Unraveling the RKIP–YY1 axis: immune crosstalk in the pathogenesis of metabolic disorders - Alzaid, Fawaz; Arefanian, Hossein; Bahman, Fatemah; Albeloushi, Shaima; Alhamar, Ghadeer; Mohammad, Anwar; Hasan, Amal; Al Madhoun, Ashraf; Ahmad, Rasheed; Al-Mulla, Fahd (Frontiers in Immunology, 2025)
Metabolic diseases, including obesity, type 2 diabetes, and cardiovascular disorders, are increasingly recognized as chronic inflammatory conditions driven by dysregulated immune-metabolic interactions. Two pivotal regulators of this crosstalk are Raf kinase inhibitor protein (RKIP) and the transcription factor Yin Yang 1 (YY1), which coordinate inflammatory signaling and metabolic stress responses across multiple tissues. RKIP exerts protective, anti-inflammatory effects by antagonizing the MAPK and NF-κB pathways, thereby preserving tissue homeostasis under metabolic stress. In contrast, YY1 acts as a context-dependent transcriptional regulator that promotes inflammatory gene programs, contributes to maladaptive immune cell differentiation, and exacerbates metabolic dysfunction. Notably, RKIP and YY1 are reciprocally regulated: RKIP suppresses YY1 expression via NF-κB inhibition, whereas YY1 represses RKIP transcription through a Snail-dependent feedback loop. In metabolic disease states, this balance is disrupted, RKIP is downregulated, and YY1 is upregulated, leading to heightened immune activation, cytokine production, and tissue damage. Therefore, we propose that RKIP and YY1 represent two opposing yet dynamically coordinated regulators of immunometabolic balance, functioning as a molecular rheostat that determines whether immune responses shift toward inflammation or resolution under metabolic stress. This review synthesizes current insights into the molecular structures, signaling pathways, and tissue-specific functions of RKIP and YY1, emphasizing their interplay in shaping immune responses in metabolic disorders. We further discuss emerging therapeutic approaches aimed at restoring RKIP–YY1 homeostasis to mitigate chronic inflammation and metabolic pathology.